2002
DOI: 10.1265/ehpm.2002.123
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical strength, cerebral function and mental health in independent-living elderly Japanese women

Abstract: Objectives: To evaluate the physical strength, cerebral function, and mental health conditions in elderly persons, and to examine the correlation between these functions.Methods: The subjects were 151 independent-living elderly Japanese women, mean age 70 +/ 5 years (+/ SD; range, 60 to 80 years), with normal abilities in daily life. The health check-up was conducted from April to May 1997. Physical strength was estimated by measuring seven activities. Cerebral functions were assessed by six sub-tests of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…After discussion, an agreement was reached, or a consensus was established with the third author. After the full-text reading and analysis of the 136 full texts, 49 studies were included in the final analysis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After discussion, an agreement was reached, or a consensus was established with the third author. After the full-text reading and analysis of the 136 full texts, 49 studies were included in the final analysis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 24 [ 58 ] to 10 092 [ 60 ] older adults, whereas the average of the 49 studies was 1030 participants. Six studies gathered samples which included 100% of older adult women [ 34 , 45 , 55 , 64 , 68 , 73 ], and one study sampled only men [ 66 ]; the percentage of women in the study samples was between 47% [ 76 ] and 81.4% [ 70 ]. Among the studies that identified the age range, an interval between 60 and 105 years was reported, with a minimal sample-age average of 67.4 years [ 41 ] and a maximal of 80 years [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that patients unable to sustain one-legged balance for 5 s with their eyes closed are 2.1 times more likely to fall than those who can maintain balance for more than 5 s ( Vellas et al, 1997 ). Additionally, the time spent on SCST was negatively correlated with somatic symptoms and anxiety/insomnia ( Hayashi et al, 2002 ). The SCST can enhance the arterial resilience of the supporting leg ( Zhou et al, 2022 ), thereby fostering cardiovascular well-being and preventing cardiovascular diseases in older women.…”
Section: Discussionmentioning
confidence: 99%